2017
DOI: 10.1021/acsearthspacechem.7b00064
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Thermal Reactions of Sulfur Dioxide on Ice Surfaces at Low Temperature: A Combined Experimental and Theoretical Study

Abstract: The interaction of sulfur dioxide (SO 2 ) gas with a crystalline ice surface at low temperature was studied by analyzing the surface species with low energy sputtering (LES) and reactive ion scattering methods and the desorbing gases with temperatureprogrammed desorption mass spectrometry. The study gives direct evidence for the occurrence of efficient hydrolysis of SO 2 with low energy barriers on the ice surface. Adsorbed SO 2 molecules react with the ice surface at temperatures above ∼90 K to form anionic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…The surface propensity of excess protons is well supported by theoretical calculations. ,,,, Density functional theory (DFT) calculations indicate that the hydronium structure is energetically stabilized at the ice surface compared with that in the tetrahedral ice lattice. ,, The calculated surface segregation energy of hydronium varies sensitively with respect to the local structure of the ice surface, particularly the spatial arrangement of dangling surface hydrogens, in a wide range of 20–80 kJ mol –1 . Hydroxide is also stabilized at the ice surface with a comparable magnitude of surface segregation energy .…”
Section: Protons At the Surfacementioning
confidence: 85%
“…The surface propensity of excess protons is well supported by theoretical calculations. ,,,, Density functional theory (DFT) calculations indicate that the hydronium structure is energetically stabilized at the ice surface compared with that in the tetrahedral ice lattice. ,, The calculated surface segregation energy of hydronium varies sensitively with respect to the local structure of the ice surface, particularly the spatial arrangement of dangling surface hydrogens, in a wide range of 20–80 kJ mol –1 . Hydroxide is also stabilized at the ice surface with a comparable magnitude of surface segregation energy .…”
Section: Protons At the Surfacementioning
confidence: 85%
“…Therefore, the configurational entropy of protons may operate for a range of ice-related phenomena involving proton transfer. For example, hydrolyses of HF (p K aq = 3.2) and SO 2 (p K aq of H 2 SO 3 = 1.9) in ice at low temperature have been observed. Ayotte and coworkers explained this reactivity of HF in ice by suggesting that HF is intrinsically a strong acid; its weak acidity in aqueous solution results from the large negative entropy of F – hydration.…”
mentioning
confidence: 99%
“…Programmed heating of the physisorbed gas to 120 K causes desorption from the ice surface and thus separates it from the chemisorbed hydrolysis products. Quantum chemical calculations suggest that the mechanism of formation of these products is similar to the equations outlined above (Bang et al 2017).…”
Section: Thermal Processingmentioning
confidence: 68%
“…Recent work by Bang et al (2017) has also shown that thermally-driven reactions between H2O ice and gas phase SO2 are possible. Their study showed that SO2 molecules adsorbed at the surface of a H2O ice can react with the ice at temperatures of > 90 K. The primary reaction products are SO2 -, HSO3 -, and OH -.…”
Section: Thermal Processingmentioning
confidence: 99%